Toward characterization of perceptual specialization for faces in Multiracial contexts - Pickron, Charisse B.; Kutlu, Ethan (Frontiers in Psychology, 2024)
This conceptual analysis focuses on opportunities to advance research and current hypotheses of perceptual development by examining what is presently known and unknown about perceptual specialization in a Multiracial context during the first year of life. The impact of being raised in a Multiracial family or community is discussed to further characterize the development of perceptual expertise for faces and languages. Historical and present-day challenges faced by researchers in defining what race is, identifying Multiracial individuals or contexts, and how to study perceptual and cognitive processes in this population are discussed. We propose to leverage current data from developmental Multilingual populations as a guide for future research questions and hypotheses characterizing perceptual specialization based on face race for Multiracial/Multiethnic individuals and contexts. Variability of input and the pattern of specialization are two factors identified from the developmental Multilingual literature that are likely useful for studying Multiracial contexts and development. Several methodological considerations are proposed in hopes of facilitating research questions and practices that are reflective of and informed by the diversity of experiences and social complexities within Multiracial populations.